الاستقصاء عن ترسيب الزنك في أعقاب ادمصاصه في الترب الكربوناتية (الكلسية) والبازلتية - عجيب, علي; جركس, فريال (Latakia University Journal -Biological Sciences Series, 2019)
The aim of this study was to evaluate the distribution of zinc among solute, adsorbed and precipitated phases in calcareous and basaltic soils. For this purpose, the results of sorption batch experiment, conducted at pH = 6 ± 0.2, have been investigated using Freundlich and Langmuir equations and combining a thermodynamic approach and X-ray diffraction (XRD) spectroscopy. It has been shown that both Freundlich and Langmuir models fit similarly well the data of zinc uptake, and corroborates the hypothesis that Banias soil expresses more affinity for zinc retention. The exponential evolution of distribution coefficient KD with ZnTOT indicates that higher affinity is expressed at low degrees of coverage. The partitioning among zinc species in solution indicated that the free ions of zinc Zn2+ were the most dominant in solution. The predictions based upon the thermodynamic calculation, and the evidences provided by XRD spectroscopy corroborate and show both the precipitation of zinc as franklinite ZnFe2O4. This mineral hence may deeply affect the dynamic of zinc in natural environment in presence of iron minerals. هدفت هذه الدراسة إلى حصر ميزانية الزنك والتنبؤ بترسيبه في ترتين متباينتين بقوامهما وبتركيبهما الفلزي: تربة كربوناتية (كلسية) وتربة بازلتية. وبحثاً عن هذه الميزانية درست إزاحة الزنك من قبل التربتين بصورتهما الصوديومية (تربة – (Na عند قيمة للـ pH = 6 ± 0.2 وذلك كتابع للتركيز (0.00025- 0.02 مول/لتر) في معلقات نسبها 1g : 25 ml. وبتحليل النتائج تطبيقاً لعلاقتي فرندليش ولانغمير تبين أن العلاقتين تتنبآن بإزاحة الزنك بكفاية عالية، وتدلان على أن تربة بانياس تزيح هذا العنصر باصطفائية أعلى، متفقتين بذلك مع مدلول معامل التوزع KD ، الذي رسم مساراً أسياً متصاعداً بانخفاض التركيز الكلي للزنك. وأظهرت حسابات التوازن الترموديناميكي من ناحيتها السيادة شبه المطلقة لشاردة الزنك في المحلول. كما بيّنت هذه الحسابات أن الفرانكلينيت ((ZnFe2O4 متبوعاً بـ "زنك- التربة" والولميت ((Zn2SiO4 كانت الأطوار الفلزية القابلة للترسيب. فيما ظهرت أطوار أخرى كالسميثونيت ((ZnCO3 والهوبيت ( (Zn3(PO4)2.4H2O والهيدروكسيدات (Zn(OH)2) غير مستقرة. وهذه النتيجة القائمة على حسابات ترموديناميكية خالصة أكدتها بطريقة ما نتائج التحليل بالأشعة السينية (XRD) التي كشفت عن تمايز الفرانكلينيت بصورتيه، المتبلورة النهائية (ZnFe2O4) أو الانتقالية(Fe6.8 Zn3.2) ، وكذلك الزنسيت. انطلاقاً مما تقدم يمكن التأكيد على أهمية الفرانكينيت ودوره النوعي فيما يخص ديناميكية معدنه في الأوساط الطبيعية وبالأخصّ تلك التي تتميّز بمحتواها العالي من أكاسيد الحديد.